IgE Immune Complexes Mitigate Eosinophilic Immune Responses through NLRC4 Inflammasome - Ece Oylumlu; Goksu Uzel; Lubeyne Durmus; Ceren Ciraci (Mediators of Inflammation)
Immune complexes (ICs) skew immune responses toward either a pro- or anti-inflammatory direction based on the type of stimulation. Immunoglobulin E (IgE) is associated with Th2 immune responses and known to activate innate immune cells. However, roles of antigen (Ag)-specific-IgE ICs in regulating human eosinophil responses remain elusive; therefore, this study builts upon the mechanism of which ovalbumin (Ova)-IgE ICs affects eosinophilic responses utilizing human EoL-1 cell line as a model. Eosinophils are granulocytes functioning through pattern recognition receptors (PRRs) and destructive granule contents in allergic inflammation and parasitic infections. One of the PRRs that eosinophils express is NLRC4, a member of the CARD domain containing nucleotide-binding oligomerization (NOD)-like receptor (NLR) family. Upon recognition of its specific ligand flagellin, NLRC4 inflammasome is formed and leads to the release of interleukin-1β (IL-1β). We exhibited that Ova-IgE ICs induced the NLRC4-inflammasome components, including NLRC4, caspase-1, intracellular IL-1β, and secretion of IL-1β, as well as the granule contents MMP9, TIMP1, and TIMP2 proteins via TLR2 signaling; these responses were suppressed, when NLRC4 inflammasome got actived in the presence of ICs. Furthermore, Ova-IgE ICs induced mRNA expressions of MMP9, TIMP2, and ECP and protein expressions of MMP9 and TIMP2 in EoL-1 through FcɛRII. Interestingly, TLR2 ligand and Ova-IgE ICs costimulation elevated the number of CD63+ cells, a degranulation marker, as compared to the native IgE. Collectively, our findings provide a mechanism for the impacts of Ova-IgE ICs on eosinophilic responses via NLRC4-inflammasome and may help understand eosinophil-associated diseases, including chronic eosinophilic pneumonia, eosinophilic esophagitis, eosinophilic granulomatosis, parasitic infections, allergy, and asthma.